GLOBALIZATION AND HIGHER EDUCATION: A WAY TO THE GLOBAL CITIZENSHIP OR LOSS OF NATIONAL IDENTITY - T. L. Oskolova (Образование и наука)
The paper considers the influence of globalization (both its positive and negative effects) on higher education systems worldwide including the USA and Russia. The research analyzes the potential of higher educational institutions for raising students’ capability of living and working in the global environment, which implies both raising the global competencies and preserving the traditional national and cultural values. Applying the comparative historical method, the author traces the US history that combines the “macdonaldization” period and long records of poly-cultural social interactions and cross-cultural adaptations. As an alternative to the existing pragmatic approach, the author puts forward the multicultural educational paradigm which is a culture relevant, valuebased system of moral and civil education focused on preservation of unique national features and simultaneous development of universal human values. The research objectives include critical evaluation of the USA experience, regarding the advantages and disadvantages of commercialized education; and identification of the pragmatic approach consequences in Russia, such as unification and simplification of education, and negative impact on the cultural and national identity formation. The research findings could be used for developing the higher education strategy as well as the curriculum on globalistics, multicultural education, and cross-cultural communications.